PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN WAJIB PAJAK DI KANTOR PELAYANAN PAJAK JAKARTA UTARA - Heryanto, Wawan (Perspektif : Jurnal Ekonomi dan Manajemen Akademi Bina Sarana Informatika, 2012)
This study aimed to test whether the independent variable (Reliability, Responsiveness, Assurance, Empathy, physical manifestation) have an influence on the dependent variable (satisfaction taxpayer) partially or simultaneously. Of 6 (six) Primary Jakarta Tax Office in North Jakarta who meet the criteria in this study took the 6 (six) Primary Jakarta Tax Office in North Jakarta. As KPP Primary Sunter Jakarta, Jakarta Head Ivory Primary KPP, KPP Primary Penjaringan Jakarta, Jakarta Koja Primary KPP, KPP Jakarta Pademangan Primary, Primary KPP Jakarta Tanjung Priok. Questionnaires that have been netted, filled with as many as 60 pieces of questionnaire respondents taxpayers who reported SPT (the Notice) Personal and SPT (the Notice) The Agency Tax Services Office in North Jakarta. The results obtained by multiple linear regression analysis equation Y = 50930 + .416 + 2.806X2 XI + X4 +027 + 260X3 + e 1.123X5 Reliability, Responsiveness, Assurance,Tax effect on satisfaction, while there is no influence of empathy and physical form in Simultaneous Test results show that the variable Reliability, Responsiveness, Assurance, Empathy, Being physical effect on taxpayer satisfaction. The coefficient of determination (R2) showed that the satisfaction of the taxpayer is equal to 60.CJO/o is determined by the variable Reliability, Responsiveness, Assurance, Empathy, Being physically while the remaining 39.1% is influenced by other variables outside the study.